Measuring China's patent quality: Development and validation of ISR indices - Philipp Böing; Elisabeth Müller (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Because China has become one of the largest applicants of PCT patents, it is of interest to compare the quality of Chinese and non-Chinese applications. We extend a quality index based on internationally comparable citation data from international search reports (ISR) to consider foreign, domestic, and self citations. Whereas foreign citations show that Chinese PCT patent applications reach only a third of the non-Chinese quality benchmark, the extension towards domestic and self citations suggests a higher quality level that converges to or even surpasses the benchmark. We investigate these differences based on firm-level regressions and find that in China, only foreign citations, but not domestic and self citations, have a significant and positive relation to R&D stocks. Using Germany as a representative country without policy support for patenting, we show that all three citations types may be used as economic indicators if policy distortion is not a concern. Our results show that domestic and self citations suffer from an upward bias in China and should be employed with caution if they are to be interpreted as a measure of patent quality.
Keywords: O34; O3; 330; patent quality; cross-country comparison; China